Assessment of seismic drift of structural walls designed according to SANS 10160 - Part 4 - Le Roux, Rudolf Cornelis (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Civil Engineering))--University of Stellenbosch, 2010.